Intestinal malrotation with solitary jejunal diverticulum presenting as midgut volvulus in an adult: an unusual presentation - Chatterjee, Debarghya; Raul, Subrat Kumar; Patras, Elisheba (International Surgery Journal, 2021)
Intestinal malrotation with midgut volvulus presenting in adults is a rare entity, and association with jejunal diverticulum is rarer still. Herein, we report and review such a case of malrotation and volvulus, associated with intestinal band adhesions and a solitary jejunal diverticulum. This 67 years old gentleman had presented with complaints of intermittent abdominal pain for past several years. Imaging of the abdomen revealed twisting of superior mesenteric artery and vein, evidence of midgut volvulus and intestinal malrotation with “whirlpool sign”. Laparotomy revealed a midgut volvulus, extensive adhesions involving the root of the mesentery and a jejunal diverticulum. Adhesiolysis was performed, untwisting of the bowel was done and the jejunal diverticulum was resected. Post-operative period was uneventful. This case is being reported on account of its extreme rarity.